Dietary Quercetin Regulates Gut Microbiome Diversity and Abundance in Apis cerana (Hymenoptera Apidae) - Haodong Wu; Conghui Ji; Ruisheng Wang; Lijiao Gao; Wenhua Luo; Jialin Liu (Insects)
Honeybee gut microbiota plays a crucial role in maintaining their health and digestive function. Studies have confirmed that quercetin improves honeybee health by enhancing their pesticide tolerance and survival rates. This study aimed to examine the effects of quercetin on the bee gut microbiome by absolute quantification sequencing. We included 1800 bees from the experimental apiary and exposed them to 151.2, 75.6, and 37.8 mg/L of quercetin. Gut samples were collected on the 5th and 9th days, subjected to a polymerase chain reaction and 16S rRNA sequencing, and analyzed. After 5 days of quercetin treatment, the diversity of the honeybee gut microbiota was altered, and total bacterial copies and Lactobacillus abundance significantly decreased at high quercetin concentrations (151.2 and 75.6 mg/L). On day 9, the gut microbial community had recovered from the adverse effects, and Gilliamella abundance increased in response to 37.8 mg/L quercetin treatment. However, quercetin had no noticeable effects on survival rate, food consumption, and gut structure. Our study confirmed the effect of short-term quercetin intake on the gut microbiota of A. cerana, providing valuable insights into how phytochemicals alter the bee gut microbiome, and their repercussions on host physiology.